Analisis Keandalan Trafo 2000 kVA dan Panel kubikel 20 kV melalui Preventive Maintenance PT Surya Toto Indonesia Tbk - Triyatne, Yuninda; Aribowo, Didik (SURYA TEKNIKA, 2025)
Electrical distribution systems constitute vital infrastructure in manufacturing operations requiring high reliability levels to ensure production continuity. This study evaluates the performance of a 2000 kVA transformer and 20 kV cubicle panel at PT Surya Toto Indonesia, Tbk through reliability parameter analysis based on preventive maintenance strategies. A quantitative descriptive method was applied by collecting operational data during July-August 2025 covering 1,464 operating hours. Measured parameters included oil temperature, oil level, input/output voltage, load current, along with failure documentation and repair duration. Reliability analysis employed Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and Availability calculations following IEEE Std 493-2017 standards. Research findings demonstrate the transformer achieved MTBF of 360 hours, MTTR of 4.5 hours, and availability of 98.8%, while the cubicle panel obtained MTBF of 292.8 hours, MTTR of 5 hours, and availability of 98.3%. Both availability values exceed Indonesian manufacturing industry standards (>95%) and approach world-class manufacturing category (>98%). Scheduled preventive maintenance programs encompassing daily inspections, weekly, monthly, and annual maintenance proved effective in reducing failure frequency. The study recommends implementing IoT-based condition monitoring and SCADA system integration to enhance reliability toward a 99% target.